Emotional Dependency And Coping Strategies In Dating Relationships In Peruvian University Students - Tezén, Angélica Lourdes Niño; Alva, José Melanio Ramírez; Merino, Carlos Eduardo Juárez; Ruiz, Shirley Lisbet Peña; Flores, Francisco Alexandro Ramos; Villar, Miguel Ángel Saldarriaga (Migration Letters, 2024)
In the specialized literature, the relationship of emotional dependence with dating violence in general has been studied, but few studies have been concerned with relating it to coping strategies, especially in university students, in this sense the research aimed to determine to what extent coping strategies predict emotional dependence in dating relationships. It is a basic study with a non-experimental design of causal correlational scope, the sample was 286 university students of both sexes, the Emotional Dependency Inventory and the BriefCope 28 Coping Scale were applied, according to the results an R of 0.580 was obtained, the R-squared is 0.337 and the adjusted R-squared is 0.334, This is interpreted as a low positive causal correlation between the variables, in addition to significant differences of 0.02 < 0.05 between men and women, being the first to obtain higher scores in emotional dependence. It is concluded that the strategies used by young people to face various situations, specifically in the field of love, do not necessarily predict emotional dependence on their partner, so it is noteworthy that further research investigates the causal relationship between emotional dependence and self-esteem, self-concept or social skills.